Empowering youth lasting change; SEED-SCALE a process to youth engagement and sustainable development - Mallick, Shahid; Mazibar Rahman, (Technium Social Sciences Journal, 2020)
For sustainable development and meaningful changes in society, the use of human energy is a must. In the question of the use of human energy one-third of human energy is untapped or not addressed properly and this constitutes the youth. However, to utilize these very human energies there is a need for policy, education, training, participation, equitable access to resources, and process of empowerment. And for the optimum utilization of youth energy, the diversity & complexity of the issue need to be understood from a holistic perspective. The main objective of this paper is to look for ways and means of youth empowerment and community development. The methods used in this research are descriptive surveys, observation, personal interviews, and focus group discussions (FGD).